Redefining success : social justice and the ends of business - Zorn, Gwendolyn Philippa (Rhodes University, Faculty of Humanities, Department of Philosophy, 2014)
Success in business is for the most part defined in financial terms and, because of this, business operations are almost entirely, if not entirely, directed to this end. The principle behind this rationale has been informed by the thought that the best contribution businesses can make to social justice is to focus on the bottom line. By appealing to enlightened self-interest and the high premium people place on freedom, neoliberal economists like Milton Friedman and Friedrich Hayek argue that maximising profits is necessarily socially responsible. And, moreover, that not to pursue this end is socially irresponsible. Social responsibility is the ultimate justification that thinkers such as Friedman and Hayek appeal to when claiming that the business of business is to maximise profit. Yet this position is internally inconsistent. The position is ultimately justified by what is socially just but this means that in fact social justice, and not profit-making, ought to be the end of business. I shall argue that taking this commitment seriously involves rejecting the idea that the aim of business is to maximise profits. This is not to say that businesses should not make profits, rather it implies that this feature is not what ultimately makes them successful. The central contribution of this project is to resolve the contradictions embedded in the traditional approach to business by arguing that the primary aim of business is the promotion of social justice. To this end success in business needs to be redefined so that it reflects the achievement of its ultimate ends and not simply its instrumental means (profit) to the realisation of these aims. We ought then to revise our fundamental assumptions about the structures and policies that are necessary for business to achieve its real end of social justice.
Keywords: Success; Social justice; Success in business; Social responsibility of business; Business ethics; Corporate profits